2022
DOI: 10.1021/acs.jpcc.2c02978
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Absorption and Hot Carrier Trapping in Anatase TiO2: The Role of Surface Oxygen Vacancies

Abstract: Anatase TiO 2 is an efficient water splitting photocatalyst using UV light, but solar energy harvesting requires the presence of midgap states to increase visible light absorption. Despite numerous studies, important questions remain regarding the photophysics in O vacancy doped TiO 2 . By employing extreme ultraviolet reflection−absorption (XUV-RA) spectroscopy at the Ti M 2,3 -edge, spectral signatures of both large and small polaron states are identified, allowing ultrafast electron and hole dynamics in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 88 publications
(103 reference statements)
1
8
0
Order By: Relevance
“…Pico-second time-resolved luminescence measurements have shown that the decay time constant of the luminescence of STEs in anatase nanoparticles is around 46 ps. 14 Transient absorption measurements have revealed that the decay time constant of the luminescence is much slower than that of the formation of trapped holes (<200 fs 24 and 45 ± 42 fs 25 ) and much faster than the lifetime of trapped holes (>1 μs). 26 This indicates that the majority of free holes produced after the adsorption of light immediately undergo to the trap sites, and the remaining free holes bind with an electron to produce STE leading to luminescence (Figure 3).…”
Section: Anatase Tiomentioning
confidence: 99%
“…Pico-second time-resolved luminescence measurements have shown that the decay time constant of the luminescence of STEs in anatase nanoparticles is around 46 ps. 14 Transient absorption measurements have revealed that the decay time constant of the luminescence is much slower than that of the formation of trapped holes (<200 fs 24 and 45 ± 42 fs 25 ) and much faster than the lifetime of trapped holes (>1 μs). 26 This indicates that the majority of free holes produced after the adsorption of light immediately undergo to the trap sites, and the remaining free holes bind with an electron to produce STE leading to luminescence (Figure 3).…”
Section: Anatase Tiomentioning
confidence: 99%
“…In fact, the effect of intrinsic oxygen vacancies on the rates of electron and hole trapping in anatase/ brookite/rutile TiO 2 , WO 3 , and α-Fe 2 O 3 has only recently been established. 11−16 Charge separation and carrier transport to the surface depend on carrier mobilities and the extent of localization into polarons, which is an area of the current experimental 11,16,17 and theoretical 18−20 study.…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental understanding of the electronic structure of dopant-induced defects and procedures to prepare well-characterized materials is necessary for direct measurement of electron dynamics and other factors that determine the quantum efficiency. In fact, the effect of intrinsic oxygen vacancies on the rates of electron and hole trapping in anatase/brookite/rutile TiO 2 , WO 3 , and α-Fe 2 O 3 has only recently been established. Charge separation and carrier transport to the surface depend on carrier mobilities and the extent of localization into polarons, which is an area of the current experimental ,, and theoretical study.…”
Section: Introductionmentioning
confidence: 99%
“…They create in-gap localized energy levels near the conduction band minimum 45 . Oxygen vacancies increase the visible light absorption by generating inter sub-band energy states so photons with less energies than the TiO 2 band gap can be absorbed 44 , 46 , 47 . Moreover, It is known that the presence of oxygen vacancies and/or the Ti 3+ oxygen vacancy associates in the TiO 2 changes the color of the material from withe to yellow, blue, black or red 48 , 49 .…”
Section: Introductionmentioning
confidence: 99%